THE ROLE OF CELEBRITY ENDORSEMENT, CONTENT MARKETING, AND PRODUCT QUALITY ON PURCHASING DECISIONS OF ULTRA MILK BRAND UHT MILK PRODUCTS - Chusnah, Yunia Najachatul; Indayani, Lilik; Kumara Adji Kusuma; Rizky Eka Febriansah (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to determine the effect of Celebrity Endorsement, Content Marketing, and Product Quality on Purchasing Decisions for Ultra Milk brand UHT milk products. Method: This study uses a quantitative method. The population used is people who live in Sidoarjo, especially people who have purchased Ultra Milk brand UHT milk products. The number of samples in this study was 100 respondents, taken using a questionnaire with a purposive sampling method. Data analysis in this study used IBM SPSS Statistics Version 26 for Windows. Results: The results of this study indicate that Celebrity Endorsement has a negative and insignificant effect on Purchasing Decisions, Content Marketing has a positive and significant effect on Purchasing Decisions, and Product Quality has a positive and significant effect on Purchasing Decisions. Novelty: This study offers a unique contribution by simultaneously examining the effects of Celebrity Endorsement, Content Marketing, and Product Quality on purchasing decisions in the context of a specific local market—Ultra Milk UHT products in Sidoarjo. The findings highlight a surprising insight that Celebrity Endorsement, despite its common use in marketing strategies, has a negative and insignificant impact on consumer purchasing decisions in this case.